Development, validation and effectiveness Interactive learning materials in teaching Grade 10 Science - Balabbo, Heidie G.; Rody F. Buenviaje (2025)
The fast-paced advancements in science and technology are transforming the way people work, govern, and live, making it essential for education systems to evolve. This study aimed to develop, validate, and effectiveness of Interactive Learning Materials in teaching Science 10 using Word Wall. It specifically focused on Physics, which was identified as the least mastered competency based on the diagnostic test conducted at the beginning of School Year 2023-2024. The study was conducted at New Era High School, Tandang Sora Avenue, Quezon City, during the second quarter of School Year 2024-2025. A mixed-method research design was employed, integrating quantitative and qualitative approaches. Findings revealed that students in all groups demonstrated improvement in their Science 10 competencies, with the experimental groups showing significantly higher gains after using the Interactive Learning Materials with Word Wall. While the control group improved through conventional teaching methods, their progress was less substantial compared to those who engaged with interactive and visually engaging strategies. The results further confirmed that active learning approaches enhanced students' retention, understanding, and application of scientific concepts. Statistical analysis confirmed a highly significant difference in the posttest performance of the experimental and control groups, leading to the rejection of the null hypothesis. It is recommended that Science 10 teachers integrate Interactive Learning Materials with Word Wall strategies to enhance student engagement and mastery, particularly in Physics.
Graduate Study Thesis